Design and fabricate of high sensitivity sensor holder - Muhamad Fahrid, Abd Wahid (2012)
This report shows the design and fabrication of a high sensitivity sensor holder. The objective of the report is to design and fabricate a high sensitivity sensor holder. This report also described the high sensitivity sensor holder which is beneficial to the end users. Design generation is showed and solid three dimensional structures modelling of the high sensitivity sensor holder was developed with computer aided design software. This report also explains the fabrication process that is needed for this project. Material that is being used in this project is aluminium sheet metal, screw, and spring. The problem encountered during completion of this project is also shown in the report. An idea of improvement for the high sensitivity sensor holder is also provided for further improvement of the high sensitivity sensor holder